Narrative Policy Analysis: Utilization of Dimethyl Ether as an LPG Mixed Fuel (Case Study in Indonesia) - Reza Suraputra; Bernardus Yuliarto Nugroho (Borong Newinera Publisher, 2024)
Dimethyl Ether (DME) utilization as an LPG fuel mix policy has become a polemic among several groups. The purpose of this research is to analyze the effectiveness of narrative constructed by Government, analyze the counter narrative, and formulate a strategy to strengthen the Government narrative regarding the use of DME as an LPG mixed fuel. This research uses the Narrative Policy Analysis (NPA) method. The counter narrative is compared with Government narrative to obtain a meta narrative. The level of analysis in this research is meso. The conclusions from this research are: 1) Indonesia Government continues to use DME as a mixed fuel for LPG; 2) The obstacles of policy narrative constructed by the Indonesia Government are differences viewpoints regarding the availability and use of coal as raw material for DME and differences in belief system regarding greenhouse gas emissions. The recommended strategy to strengthen the Government’s policy narrative are: 1) Comprehensive discussion by involving groups that oppose the narrative, 2) present the result of the feasibility study on greenhouse gas emmision resulting fro DME production process from coal which has been carried out by the Government by providing socialization regarding tax policy carbon as well as technical implementation of carbon economic value and controlling greenhouse gas emmision.